Oxidation affects dye binding of myofibrillar proteins via alteration in net charges mediated by a reduction in isoelectric point. (January 2023) - Yu, Qingqing; Shi, Tong; Xiong, Zhiyu; Yuan, Li; Hong, Hui; Gao, Ruichang; Bao, Yulong
Graphical abstract: Highlights: Myofibrillar proteins shifted to a more acidic isoelectric point upon oxidation. Oxidation led to decreased or increased net charges of proteins depending on pH. Dye-binding between proteins and differently charged dyes was investigated. Oxidation-induced change in net charge is driving force affecting the dye-binding. Abstract: In order to study the effect of oxidation on the dye-binding behavior of myofibrillar proteins, selected dyes with different charges (positively charged Sarfarin O (SO), neutral bromophenol blue (BPB), and negatively charged Orange G (OG)) were incubated with myofibrils oxidized by the Fenton system with H2 O2 (10 mM). Upon oxidation, loss of free thiols, formation of carbonyls, particle size, and hydrophobicity of myofibrillar proteins (MPs) increased. The absolute value of Zeta-potential increased by 14.48 % after oxidation, the myofibrillar proteins shifted to a more acidic isoelectric point (pI) upon oxidation. Oxidation decreased net positive charges of myofibrillar protein and the binding ability of MPs towards OG in the environment with pH less than pI and the affinity of MPs towards SO in the environment with pH more than pI were thus increased. Here we propose a hypothesis that oxidation-induced change in net charges is the driving force affecting the amount of protein-bound dye. This paper aims to examine the effect of oxidation on the net charges of myofibrillar proteins and to provide insight into the mechanism of oxidation-induced changes in protein-bound dyes.